New Insights on the Glyphosate-Degrading Enzymes C-P Lyase and Glyphosate Oxidoreductase Based on Bioinformatics - Marina Giannakara; Vassiliki Lila Koumandou (Bacteria)
Bioremediation, the degradation of environmental pollutants by living organisms, has immense potential to lead to a greener planet. Bioinformatics analysis can contribute to the identification of novel microorganisms, which biodegrade contaminants, or of participating proteins and enzymes, and the elucidation of the complex metabolic pathways involved. In this study, we focus on C-P lyase and glyphosate oxidoreductase (Gox), two enzymes which degrade glyphosate, a widely used pesticide. Amino acid sequences of the two enzymes were collected from a broad range of microorganisms using the KEGG database and BLAST. Based on this, we identified additional lineages, with putative glyphosate-degrading activity, for which no glyphosate-degrading species have been reported yet. The conserved residues in each enzyme were identified via multiple alignments and mapped onto the 3D structures of the enzymes, using PyMOL, leading to novel insights into their function. As the experimental structure of Gox is still unknown, we created structural models based on three different programs and compared the results. This approach can be used to yield insights into the characteristics of potential glyphosate-degrading enzymes. Given the limited information available, such a step is important to gain further knowledge about them, which can contribute to their application in bioremediation in the future.